Political and legal situation of the area in anticipation of formation Turkestan Soviet ASSR (Journal of actual problems of jurisprudence, 2018)
The political and legal situation of area was analyzed in anticipation of formation of Turkestan Soviet ASSR. In Turkestan region on the basis of capture policy from Russia were carried out various kinds of administrative, judicial reforms. According to this basis the Turkestan region was coped under the Russian laws. Establishment of the Soviet power in Turkestan, its formation and development was a consequence of the created political and legal situation, and also revolutions and innovations in Russia.Key words: control system, administrative district, republic, executive committee, legislative activity.